PENGARUH BAURAN PEMASARAN NON KONVENSIONAL TERHADAP KEPUASAN PELANGGAN DENGAN PENDAPATAN KONSUMEN SEBAGAI VARIABEL PEMODERASI ( Studi Kasus Pada Hotel Kusuma Sahid di Surakarta) - SRIWIJIASTUTI, SRIWIJIASTUTI (JURNAL WIDYA GANECWARA, 2014)
Good quality services will influence consumers to make, a strong relationship with the company. Furthermore, this allows the company to a better understanding carefully the desires and needs of consumers, so that can meet the wants and needs of consumers. The purpose of this study are (1) Knowing the implementation of non conventional marketing mix of Sahid Kusuma Hotel services consisting of service personnel, physical infrastructure, the service process. (2) Analyze the influence of non-conventional marketing mix of Sahid Kusuma Hotel service consisting of service personnel, physical infrastructure, and service process, to customer satisfaction. (3) Knowing the influence the consumer’s income as a moderating variable to customer satisfaction. The types of data used in this study are drawn from primary data customers of Sahid Kusuma Hotel. The samples taken are 100 from populations. The results of analysis using hierarchical regression analysis techniques found that the care workers have a significant positive impact on customer satisfaction; physical infrastructure has a significant positive impact on customer satisfaction; service process has a significant positive impact on customer satisfaction; interaction service representatives and service processes with a variable income as moderating effect of consumers not influential to customer satisfaction, and the consumer’s income as a moderating effect strengthens the influence of physical infrastructure on the level of customer satisfaction of Sahid Kusuma Hotel. Given service personnel, physical infrastructure and service process has a significant influence on customer satisfaction, then the hotel management should improve these factors. Some ways that can improve the hotel management, are; Improving personnel selection and job placement, skills of staff in services, infrastructure improvement in customer service.